Self-Repair and Language Selection in Bilingual Speech Processing - Inga Hennecke (Discours)
In psycholinguistic research the exact level of language selection in bilingual lexical access is still controversial and current models of bilingual speech production offer conflicting statements about the mechanisms and location of language selection. This paper aims to provide a corpus analysis of self-repair mechanisms in code-switching contexts of highly fluent bilingual speakers in order to gain further insights into bilingual speech production. The present paper follows the assumptions of the Selection by Proficiency model, which claims that language proficiency and lexical robustness determine the mechanism and level of language selection. In accordance with this hypothesis, highly fluent bilinguals select languages at a prelexical level, which should influence the occurrence of self-repairs in bilingual speech. A corpus of natural speech data of highly fluent and balanced bilingual French-English speakers of the Canadian French variety Franco-Manitoban serves as the basis for a detailed analysis of different self-repair mechanisms in code-switching environments. Although the speech data contain a large amount of code-switching, results reveal that only a few speech errors and self-repairs occur in direct code-switching environments. A detailed analysis of the respective starting point of code-switching and the different repair mechanisms supports the hypothesis that highly proficient bilinguals do not select languages at the lexical level.